Lymphangitic sporotrichosis - Chieco, P. (European Journal of Pediatric Dermatology, 2014)
It is the most common cutaneous form of sporotrichosis, a chronic infection caused by Sporothricum schenckii, more common in people who live in the country and that affects children in 20% of cases. The fungus penetrates usually in the skin of the hands (Fig. 1, 3) or feet entering through small wounds. At the point of inoculation appears a nodule which then ulcers. When the infection is not diagnosed and treated, other nodules appear along the course of lymphatic vessels (Fig. 1, 2) towards the lymph nodes and then undergo softening and ulceration. The definitive diagnosis is made by mycological culture. The latter highlights creamy colonies that with time become brownish (Fig. 4). The microscopic examination of the colonies (Fig. 5) shows fine hyphae from which branch oval or pear-shaped conidia reminiscent of flowers.